EXPLORING BIODIVERSITY WHILE ASSISTING THE ORANG ASLI COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, February 2016 – A research team together with final-year students from the School of Biological Sciences (PPSK) Universiti Sains Malaysia (USM) recently went on a 5-day expedition to explore the biodiversity at the Royal Belum Forest Reserve in Gerik, Perak.